A propensity-matched study of the effect of diabetes on the natural history of heart failure: variations by sex and age. Issue 12 (8th May 2007) - Ahmed, Ali; Aban, Inmaculada B; Vaccarino, Viola; Lloyd-Jones, Donald M; Goff, David C; Zhao, Jiannan; Love, Thomas E; Ritchie, Christine; Ovalle, Fernando; Gambassi, Giovanni; Dell'Italia, Louis J
Abstract : Background: Poor prognosis in heart failure (HF) patients with diabetes is often attributed to increased co-morbidity and advanced disease. Further, this effect may be worse in women. Objective: To determine whether the effect of diabetes on outcomes and the sex-related variation persisted in a propensity score-matched HF population, and whether the sex-related variation was a function of age. Methods: Of the 7788 HF patients in the Digitalis Investigation Group trial, 2218 had a history of diabetes. Propensity score for diabetes was calculated for each patient using a non-parsimonious logistic regression model incorporating all measured baseline covariates, and was used to match 2056 (93%) diabetic patients with 2056 non-diabetic patients. Results: All-cause mortality occurred in 135 (25%) and 216 (39%) women without and with diabetes (adjusted HR = 1.67; 95% CI = 1.34 to 2.08; p<0.001). Among men, 535 (36%) and 609 (41%) patients without and with diabetes died from all causes (adjusted HR = 1.21; 95% CI = 1.07 to 1.36; p = 0.002). Sex–diabetes interaction (overall adjusted p<0.001) was only significant in patients ⩾65 years (15% absolute risk increase in women; multivariable p for interaction = 0.005), but not in younger patients (2% increase in women; p for interaction = 0.173). Risk-adjusted HR (95% CI) for all-cause hospitalisation for women and men were 1.49 (1.28 to 1.72) and 1.21 (1.11 to 1.32), respectively, also with significant sex–diabetes interaction (p = 0.011). Conclusions: Diabetes-associated increases in morbidity and mortality in chronic HF were more pronounced in women, and theses sex-related differences in outcomes were primarily observed in elderly patients.